On the limited recognition of inorganic surfaces by short peptides compared with antibodies. (15th April 2014) - Artzy‐Schnirman, Arbel; Abu‐Shah, Enas; Dishon, Matan; Soifer, Hadas; Sivan, Yotam; Reiter, Yoram; Benhar, Itai; Sivan, Uri
<x xml:space="preserve">Abstract</x> The vast potential applications of biomolecules that bind inorganic surfaces led mostly to the isolation of short peptides that target selectively specific materials. The demonstrated differential affinity toward certain surfaces created the impression that the recognition capacity of short peptides may match that of rigid biomolecules. In the following, we challenge this view by comparing the capacity of antibody molecules to discriminate between the (100) and (111A) facets of a gallium arsenide semiconductor crystal with the capacity of short peptides to do the same. Applying selection from several peptide and single chain phage display libraries, we find a number of antibody molecules that bind preferentially a given crystal facet but fail to isolate, in dozens of attempts, a single peptide capable of such recognition. The experiments underscore the importance of rigidity to the recognition of inorganic flat targets and therefore set limitations on potential applications of short peptides in biomimetics. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.